2007
DOI: 10.1073/pnas.0610279104
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide RNA interference screen identifies putative chromatin regulators essential for E2F repression

Abstract: Regulation of chromatin structure is critical in many fundamental cellular processes. Previous studies have suggested that the Rb tumor suppressor may recruit multiple chromatin regulatory proteins to repress E2F, a key regulator of cell proliferation and differentiation. Taking advantage of the evolutionary conservation of the E2F pathway, we have conducted a genome-wide RNAi screen in cultured Drosophila cells for genes required for repression of E2F activity. Among the genes identified are components of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 35 publications
4
91
1
Order By: Relevance
“…It will be interesting to determine whether this is a general mechanism through which the E2F-pRB pathway functions to modulate gene expression during the cell cycle and whether other transcriptional repressors share this ability to recruit L3MBTL1. Interestingly, the fly tumor suppressor L(3)mbt was also identified in a genome-wide RNAi screen for genes required for E2F-dependent repression [4]. L(3)mbt was recruited to many target genes in an E2F-dependent, but RBFindependent, manner, suggesting that an E2F-L3MBT chromatin modification and repression pathway may be functionally conserved from flies to humans.…”
Section: E2f Prb and Chromatin Compactionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be interesting to determine whether this is a general mechanism through which the E2F-pRB pathway functions to modulate gene expression during the cell cycle and whether other transcriptional repressors share this ability to recruit L3MBTL1. Interestingly, the fly tumor suppressor L(3)mbt was also identified in a genome-wide RNAi screen for genes required for E2F-dependent repression [4]. L(3)mbt was recruited to many target genes in an E2F-dependent, but RBFindependent, manner, suggesting that an E2F-L3MBT chromatin modification and repression pathway may be functionally conserved from flies to humans.…”
Section: E2f Prb and Chromatin Compactionmentioning
confidence: 99%
“…However, the identification of eight E2F family members and the development of new functional genomic approaches have accelerated our progress and proven that the function of the E2F family is substantially more complex. In addition, genome-wide approaches in mammalian cells, flies, and worms have indicated that this family controls expression of genes beyond the S phase transition and indeed beyond the cell cycle by promoting differentiation and specification of distinct tissues [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…We, and others, have found L3MBTL1 complexed with Rb/ E2F proteins repressed the activation of some E2F target genes, including c-myc and Cyclin E1, two established oncogenes (7,8,19,20). We tested whether these genes were up-regulated in L3MBTL1 knockdown cells, but noted no changes in their levels at 48 h following lentiviral infection with shRNAs against L3MBTL1 (Fig.…”
Section: Depletion Of L3mbtl1 Inhibits Cell Proliferation and Causes mentioning
confidence: 99%
“…Impairment of Cell-cycle Regulatory Gene Expression in mDomino-deficient Cells-The p400/mDomino chromatin-remodeling complex is known to interact physically or functionally with cell-cycle-regulatory transcription factors, including c-Myc, E1A, p53, and E2F (3,(17)(18)(19)(20). To gain insight into the molecular function of mDomino in cell-cycle regulation, we characterized the gene expression profiles of mDom fl/fl ;CreER MEFs treated or untreated with OHT by DNA microarray analysis (n ϭ 3 for both untreated and OHT-treated cells), which revealed that 770 genes were differentially (Ն2.0-fold) expressed by mDomino depletion, including 191 down-regulated genes (supplemental Table 1) and 579 up-regulated genes (data not shown).…”
Section: Mdomino Is Necessary For the Cell-cycle Progression Of Embrymentioning
confidence: 99%
“…This histone-exchanging activity plays a key role in the epigenetic regulation of gene expression as well as in DNA repair (12)(13)(14)(15)(16). p400/mDomino is known to interact physically and/or functionally with growth-regulating transcription factors, such as Myc, p53, E2F, and adenovirus E1A (3,(17)(18)(19)(20). In primary human fibroblasts and osteosarcoma-derived U2OS cells, the knockdown of p400/mDomino results in cell-cycle arrest at the G 1 phase with the induction of p21 expression (21,22).…”
mentioning
confidence: 99%